Pulmonary and laryngeal tuberculosis: a rare presentation in pediatrics (Archives of Pediatrics of Uruguay, 2022)
Introduction: tuberculosis (TB) is an infectious, chronic granulomatous disease caused by Mycobacterium tuberculosis. An increase in the number of cases has been reported in Uruguay, with an incidence reported in 2017 of 28.6/100,000 inhabitants, being 6.67/100,000 in children under 15 years of age. Laryngeal tuberculosis is a rare and evolved form of tuberculosis, which usually shows chronic dysphonia, which requires high levels of suspicion.Objective: to describe a clinical case with a rare presentation in pediatric age.Clinical case: 13-year-old female adolescent, healthy, fully vaccinated, with a history of active sexual behaviors and laryngeal papillomatosis diagnosed by direct laryngoscopy as a cause of chronic dysphonia. The emergency consultation was caused by abdominal pain, confirming the clinical examination weight loss associated with respiratory symptoms and bacillary toxic syndrome associated with chronic dysphonia of four months of evolution, for which laryngeal tuberculosis was considered and she was admitted for screening. She denies having been in contact with tuberculosis. The chest X-ray revealed a cavernous lesion in the left pulmonary apex and sputum smears were positive (direct and culture), confirming the suggestion of pulmonary and laryngeal TB. Supervised anti-tuberculosis treatment was performed with excellent subsequent evolution.Conclusions: tuberculosis is a re-emerging disease in our country, which requires a high level of suspicion. Its diagnosis remains a challenge for pediatricians since diagnostic confirmation is not always possible. In this clinical case, clinical suspicion of chronic dysphonia associated with respiratory symptoms were key factors to establish the diagnosis, despite not having a clear epidemiological link.
Keywords: Pulmonary tuberculosis; Laryngeal tuberculosis; Pediatrics